The survey of bacterial etiology and their resistance to antibiotics of urinary tract infections in children of Birjand city - Azita Fesharakinia; Mohammad Malekaneh; Hashem Hooshyar; Marzieh Aval; Fahimeh Gandomy-Sany (مجله دانشگاه علوم پزشکی بیرجند, 2012)
Background and Aim: Urinary tract infection is one of the most prevalent bacterial infections in childhood, which due to an inapproto determine the common bacteria and their antibiotic susceptibility in children with urinary tract infection.   Materials and Methods: This descriptive-analytical and prospective study was done in 2009-2010 on urine samples of all children under 13 years who had been referred to Emmam-Reza hospital laboratory in Birjand and had positive urine culture. Sex and age of children, the kind of isolated bacteria in urine culture, susceptibility and resistance of these bacteria to current antibiotics were studied.The obtained data was analyzed by means of SPSS using Fisher exact- test.   Results: 100 children (84 girls and 16 boys) with positive urine culture were studied. The most common age of urinary tract infection was under two years. In all ages the rate of urinary tract infection in females was more than males. E.coli was the most common cause in both sexes. There was a significant relationship between kind of microorganism and age of infection. The most prevalent cause of urinary tract infection in all ages was E.coli (75%) ,infection by Proteus was 11%, and other microorganism caused 14% of the cases. E.coli had the most susceptibility to ceftriaxone and ceftazidime and the most resistance to cephalexin and co-trimoxazol. Not taking the type of microorganism into consideration, the most sensitive antibiotics were ceftazidime, ceftriaxone, cefexim and nalidixic acid and the most resistance was against co-trimoxasol and cefalexin.   Conclusion: Regarding the results, it is recommended to use cefexime and nalidixic acid for outpatient treatment of urinary infection , and ceftazidime and ceftriaxon for inpatient treatment.Selecting of antibiotics for urinary infection therapy should be based on the local prevalence of pathogenic bacteria and antibiotic sensitivities rather than on a universal guideline.